Regioselective one-pot bromination of aromatic amines - Smith, M.B.; Guo, L.; Okeyo, S.; Stenzel, J.; Yanella, J.; LaChapelle, E. (Organic Letters, 2002)
(Matrix Presented) Treatment of aniline with n-butyllithium and then trimethyltin chloride gave the tin amide (PhNH-SnMe3) in situ. Without isolation of the tin amide reaction with bromine and workup with aqueous fluoride ion gave p-bromoaniline in 76% yield, with no dibromoaniline or o-bromoaniline. Application of this sequence to 11 different aromatic amines gave selective bromination in 36-91% yields, without formation of dibromides. This constitutes a good general method for the regioselective bromination of aromatic amines.
37 citations (Crossref) [2023-10-31]
Keywords: article; dept.che